PENGARUH MOTIVASI BERWIRAUSAHA TERHADAP PRODUKTIVITAS USAHA RUMAH MAKAN DI KELURAHAN PASAR TELUKDALAM - Halawa, Nesi Mawati (Universitas Nias Raya, 2025)
The purpose of this study was to determine the effect of entrepreneurial motivation on the productivity of restaurant businesses in Pasar Telukdalam Village. The source of data used in this study was from restaurants in Pasar Telukdalam Village by using questionnaires. The data analysis method used is simple regression analysis. Based on the results of the hypothesis testing study with a calculated value of 6,291>ttable 1.686, the researcher concluded that entrepreneurial motivation has a significant influence on the productivity of the restaurant business in Pasar Telukdalam Village with the support of the value of Y = 12,690 + 0.707X. The suggestions of this research are (1) To run a restaurant business in Pasar Telukdalam Village, motivation in entrepreneurship should be needed to be improved. (2) In increasing business productivity, restaurants in Pasar Telukdalam Village should be careful in preventing risks that will be experienced. (3) Restaurants in Pasar Telukdalam Village need to provide good communication to consumers to launch sales activities. (4) Restaurants in Pasar Telukdalam Village should allocate good expenses of income every day to find out how much profit on the sale. (5) To develop a restaurant business in Pasar Telukdalam Village, your own capital needs to be greater than the borrowed capital so as to facilitate the business.